THE IMPACT OF CHANGES TO THE PROPERTIES OF THE OILS ON THE RELIABILITY OF RAILWAY ROLLING STOCK - V. G. Danshin; O. V. Gatelyuk; S. V. Shvetsov (Вестник СибАДИ)
The authors studied a group of compressor units mounted on an updated fleet of electric locomotives. In the work of the authors of the analysis of the causes of decline in the reliability of compressors, the new series electric locomotives 2ÈS-6 «Sinara», compared with similar installations of compressed air on old series locomotives VL-10. It is shown that the major factor in reducing reliability, is changing oilings properties of materials during the operation of the compressor units. It is shown that the main factor reducing the reliability is to change the properties of lubricating materials during the operation of the compressor units.